Catalytic Partial Oxidation of Methane in Supercritical Water: A Domain in CH4/H2O-O2/CH4 Parameter Space Showing Significant Methane Coupling - Hassan, M.A. (American Chemical Society, 2017)
Partial oxidation of methane under supercritical water environment at 658 K and 26 MPa using a batch reactor was examined in the presence of metal oxide catalysts and H2O2 as a molecular oxygen source. Within a parameter space of feed concentrations (CH4/H2O and O2/CH4 ratios), there existed a domain that gave high C2+ hydrocarbon yield reaching ca. 4. Obtained products were a mixture of hydrocarbons up to C4 with ethane as a major component, accompanied by CO, CO2, H2, and methanol. The domain that gave high hydrocarbon yield did not coincide with that which gave high methanol yield. Catalyst survey indicated that transition-metal oxides are effective for the production of C2+ hydrocarbons under the present conditions. In view of the oxidative coupling of methane in all reaction modes explored previously, presently reported level of hydrocarbon yield is unprecedented at this low reaction temperature. (Graph Presented). © 2017 American Chemical Society.